Macrophage death in atherosclerosis: potential role in calcification - Neels, Jaap G.; Gollentz, Claire; Chinetti, Giulia (Frontiers in Immunology, 2023)
Cell death is an important aspect of atherosclerotic plaque development. Insufficient efferocytosis of death cells by phagocytic macrophages leads to the buildup of a necrotic core that impacts stability of the plaque. Furthermore, in the presence of calcium and phosphate, apoptotic bodies resulting from death cells can act as nucleation sites for the formation of calcium phosphate crystals, mostly in the form of hydroxyapatite, which leads to calcification of the atherosclerotic plaque, further impacting plaque stability. Excessive uptake of cholesterol-loaded oxidized LDL particles by macrophages present in atherosclerotic plaques leads to foam cell formation, which not only reduces their efferocytosis capacity, but also can induce apoptosis in these cells. The resulting apoptotic bodies can contribute to calcification of the atherosclerotic plaque. Moreover, other forms of macrophage cell death, such as pyroptosis, necroptosis, parthanatos, and ferroptosis can also contribute by similar mechanisms to plaque calcification. This review focuses on macrophage death in atherosclerosis, and its potential role in calcification. Reducing macrophage cell death and/or increasing their efferocytosis capacity could be a novel therapeutic strategy to reduce the formation of a necrotic core and calcification and thereby improving atherosclerotic plaque stability.